PENGARUH DEFERRED TAX EXPENSE DAN TAX TO BOOK RATIO TERHADAP KINERJA PERUSAHAAN MANUFAKTUR PADA SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 - Destri Syeba Stevani Sijabat; Paul Eduard Sudjiman (Jurnal Ekonomis, 2021)
This study aims to see how deferred tax expense, the tax to book ratio,on company's performance. This research was conducted on manufacturingcompanies producing the Plastics and Packaging sub-sector industry listed on theIndonesia Stock Exchange (IDX) in 2017-2020 and using a purposive sampling sampleof 12 companies for 4 years of research, the number of sampling is 48 observationaldata. The population in this study is the annual financial statements of allmanufacturers of the Plastic and Packaging sub-sector listed on the Indonesia StockExchange (IDX) 2017-2020. The analytical method used in managing data analysis isdescriptive test, normality test, multicollinearity test, heteroscedasticity test,autocorrelation test, determination test, T test and F test. Based on the results ofsimultaneous testing, deferred tax expense fan tax to book ratio has a significant effecton company performance in manufacturing companies in the Plastic and PackagingSub-Sector industry listed on the Indonesia Stock Exchange in 2017-2020.